Seroprevalencia de brucella spp, en poblaciones de ovinos en el Cantón Vinces de la Provincia de Los Ríos - Cedeño Vera, Litzy Jazmín (2023)
Because ovine brucellosis is an infectious-contagious zoonosis that produces abortions and productive and economic losses, the objective was to determine the seroprevalence, Risk Factors (RF) associated with its presence and its spatial distribution in 21 herds of Vinces sheep in the province of Los Ríos. The study was cross-sectional multistage and stratified. 248 animals were sampled from 21 Production Units (UP) according to the tables of Cornett J. and Beckner W. The animals were randomly selected between females and males. Serum samples were obtained by puncture of the jugular vein with Vacutainer equipment without anticoagulant. For the determination of risk factors, a general questionnaire and another per sampled animal were applied. From the study conducted 100% of the animals were negative for the pink bengal test by sex and age. The analysis obtained from the identified risk factors shows that the adoption of good practices in livestock management, as well as the strict implementation of biosecurity measures, have played a fundamental role in preventing the transmission of ovine brucellosis.